Sedimentology and Allostratigraphy of the Basal Belly River Formation of central Alberta - Al-Rawahi, Salim Zuwena (My University, 1993)
Abstract The nature of the transition from marine Lea Park Formation to continental Belly River Formation has been studied in a 50 m thick section in the Campanian of central Alberta. The sediments are subdivided into three allomembers (A 1 to A3), bounded by erosional discontinuities which formed as a result of relative sea level changes.
The topmost 18 m of the Lea Park Formation consists of interbedded mudstones, siltstones and sandstones, deposited in a marine offshore environment below fairweather wave base (FWWB).
Allomember 1 consists of 11 m thick sandstones with Macaronichnus traces which were interpreted as the shoreface of a prograding fluvial- and wave- dominated delta. These shoreface sandstones lie sharply on offshore mudstones of the Lea Park Formation. The lower bounding discontinuity is interpreted as a regressive surface of erosion (RSE) and consequently, the progradation of the shoreface succession of allomember 1 is due to a drop in sea level, termed a forced regression.
The sandstones of A 1 are truncated by non-marine channel sandstones, mudstones with root traces and coal beds of A2. Channel fills are up to 20 m thick and occur in a channel belt up to 20 km wide. Finegrained non-marine sediments and coal beds are restricted in the northwest of the study area. These coals are responsible for limiting the depth of erosion during the ensuing deposition of transgressive and regressive sediments of A 3.
Transgressive sediments are preserved only in A3 and comprise a 30 cm trangressive lag overlain by offshore mudstones. The extent of the lag to the northwest was mapped and found to coincide with the limit of coal deposition. Regressive sediments of A3 include fluvial and wave dominated lobate delta front sandstones, sharply overlying coal in the NW, but gradationally-based in the SE, overlying offshore mudstones. Gradationallybased shorefaces formed as a result of autocyclic delta lobe switching.
The allomembers define a fourth order cyclicity estimated at about 190,000 ka. The controls on high frequency cycles are not resolved, but A two possibilities include regional tectonics and glacio-eustasy.
Keywords: Geology; Geology